Educating the Country Out of the Child and Educating the Child Out of the Country: An Excursion in Spectrology - Corbett, Mike (Alberta Journal of Educational Research, 2006)
A focus on rurality has been largely absent from much contemporary educational policy discussion. At best, rural education is a peripheral concern just as rural areas are increasingly considered marginal to the development of a globalized, networked, fast capitalism. In Canada rural, coastal, northern, and single-industry communities that were built around primary resource extraction are constructed as social and educational problem spaces partly because their residents are often attached to these places long after they have served their economic purpose as natural resource deposits for the interests of capital. In fact rurality and rusticity are typically seen as one face of the kind of localized social condition that formal education is designed to normalize and transform by fostering outmigration and a general orientation to urban life and to mobility. In this analysis I use Derrida’s idea of spectrology to examine some images of rurality as persistent, place-attached ghosts haunting the educational project of modernity.